The effects of television on children and adolescents an annotated bibliography with an introductory overview of research results - International Association for Mass Communication Research; Schramm, Wilbur ([Paris, France] Unesco, 1964)
Following the publication by Unesco, in 1961, of an annotated international bibliography on "The Influence of the Cinema on Children and Adolescents " (Series : Reports and Papers on Mass Communication, No. 31), it was decided to produce a companion volume dealing with television.

It was felt that the preparation of this bibliography might appropriately be undertaken by the International Association for Mass Communication Research, and accordingly Unesco made a contract with that international non-governmental organization for this work. In turn, the IAMCR placed responsibility for editing the bibliography with one of its members, Dr. Wilbur Schramm.

Attention should perhaps be drawn here to the Foreword, which sets out the criteria under which, as agreed with IAMCR, items were selected. In particular, this bibliography aims at restricting itself to articles on behavioural research, that is to say publications in which the conclusions are based on experiment, survey or clinical study dealing with human behaviour. This is a narrower basis of choice than was used in the earlier bibliography on the cinema, since it is intended to exclude commentaries, however excellent, which derive from personal opinion rather than from scientific evidence.

No bibliography dealing with such a rapidly-developing medium as television can pretend to be exhaustive or definitive; but it is hoped that, despite any limitations in this respect, the present publication will serve not merely to provide useful information but will also stimulate others to supply relevant material which may be of use should an edition at a later date be found necessary.

Finally, it is pointed out that Dr. Schramm and the International Association for Mass Communication Research were responsible for the selection and presentation of the material in this publication and that any opinions expressed are those of the IAMCR and its editor, and not necessary those of Unesco.
Gift.
Keywords: Television and children -- Bibliography